MAKING APPLICATION TO CONSOLIDATED DAILY PT. TRI DHARMA WISESA USING VISUAL BASIC 6.0 - Istiyawan Pratiwanto; Sutarno, Skom, MMSI Sutarno, Skom, MMSI (Jurnal Sistem Informasi, 2006)
Scientific writing under the title "MAKING APPLICATION TO CONSOLIDATEDDAILY ON PT TRI DHARMA WISESA USING VISUAL BASIC 6.0 basicallydiscusses how to design a report making applications using Visual Basic 6.0.In this application consists of forms, databases, queries and reports presented in themain menu as an opener this application form, so users can easily operate thisapplication.With the availability of entry forms are designed in such a manner expected to allowa user to create reports more efficiently and accurately.